(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
The Indian subcontinent is incredibly rich in biodiversity and is home to many species of herpetological and conservation interest. The aim of this study was to provide a first assessment of hematological values in Travancore tortoise (Indotestudo travancorica) and red-crowned roofed turtle (Batagur kachuga), two endangered species on which medical literature is still lacking. Between May and June, 19 specimens of I. travancorica and 17 of B. kachuga were sampled. Both populations were housed by the Madras Crocodile Bank Trust – Centre for Herpetology (Tamil Nadu, India). From each animal, a blood sample (0.5 mL) was obtained from the dorsal coccygeal vein and stored in a lithium-heparin test tube. Regarding I. travancorica, from each sample was performed a complete red and white blood cell count (RBC and WBC) with the Natt & Herrik method using a Neubauer chamber, and hematocrit values were assessed using microcapillaries. Mean Corpuscular Volume (MCV) was calculated from PCV and RBC. Regarding B. kachuga, complete RBC and WBC count with the same method was performed. Due to the insufficient numerosity of both populations, only descriptive statistic was applied. Obtained values were compared with known references of other chelonians, with results consistent with those of species with similar ecological and biological characteristics.